Mental health outcomes among child welfare investigated children: In-home versus out-of-home care. (October 2015) - Conn, Anne-Marie; Szilagyi, Moira A.; Jee, Sandra H.; Blumkin, Aaron K.; Szilagyi, Peter G.
Abstract: Background: Child welfare has increasingly focused on alternatives to out-of-home (OOH) placement. In-home services, such as parent training, have increased and more maltreated children remain in-home. Yet, little is known about the effect on mental health of maintaining vulnerable children in-home vs placement in stable OOH care. Objective: To evaluate and compare difference in mental health among children investigated by child welfare and who remained in-home vs. those who were placed in stable OOH care. Design/methods: We examined a cohort of children (aged 1.5–18 years) from a nationally representative sample of children investigated by child welfare using the National Survey of Child and Adolescent Well-Being II (NSCAW II). We compared changes in mental health functioning over 18 months for children who remained in-home with parent training versus those placed in stable OOH care. Results: Among the 749 children in our sample, baseline characteristics of children who remained in-home with parent training and those placed in stable OOH care were similar. Among school-aged children placed in stable OOH care, mental health problems decreased from 26% to 13% ( p = .003). This differed significantly from school-aged children who remained in home, for whom mental health problems increased (50% decrease stable OOH care vs. 23% increase in home; p = .007). Among pre-school aged children, mental health problems increased in both settings, particularly stable out-of-home care ( p = .008). Conclusions: For school aged children with a history of maltreatment, mental health outcomes improve following stable OOH placement, yet worsen when remaining in-home with parents. Pediatricians should be watchful for mental health problems among children who remain home after maltreatment and should advocate for high-quality stable OOH care when it is necessary. Child welfare may need to monitor the outcomes of children remaining at home more closely and provide more intensive preventive and treatment services to families. Highlights: Children who remained in-home with parent training and those in stable OOH placements had similar levels of baseline risk There was a trend toward rising mental health (MH) problems among children in-home versus declining problems among those in stable OOH care School aged children had better mental health outcomes when in stable OOH care, despite the additional trauma of removal Pre-school aged children may be particularly vulnerable, as MH problems increased in both settings